2014
DOI: 10.1093/pubmed/fdu021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of implementation, compliance and acceptance of partial smoking bans among hospitality workers before and after the Swiss Tobacco Control Act

Abstract: Tobacco bans in Swiss hospitality venues are still in a period of consolidation. The incomplete nature of the law may also have had a negative impact on the development of greater acceptance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The same pattern of results was found in other studies. Smoking bans in Switzerland gained acceptance over time in areas with strict regulations and were less accepted in areas with less stringent regulations (Rajkumar et al, 2014). Participants evaluated mobile phone use while driving more negatively when they thought that a ban on this behavior would definitely come into effect compared to those who did not (Laurin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The same pattern of results was found in other studies. Smoking bans in Switzerland gained acceptance over time in areas with strict regulations and were less accepted in areas with less stringent regulations (Rajkumar et al, 2014). Participants evaluated mobile phone use while driving more negatively when they thought that a ban on this behavior would definitely come into effect compared to those who did not (Laurin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, hospitality venues improved less. Protection from SHS for employees in hospitality venues still remains inconsistent and suboptimal, as the Swiss Federal law for protection against passive smoking from 2010 still allows exemptions from the smoking ban in this sector [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, for successful implementation of a new law (such as the ban on smoking in closed public places), the target population should accept and comply with the new regulations 9 . A recent study conducted post-ban in Switzerland reported that acceptance and compliance of hospitality workers were higher in strictly smoke-free areas 10 . Moreover, there is still a vast disparity in compliance between developed and Tobacco Prevention & Cessation developing countries who have tobacco control policies in place, whether comprehensive or not.…”
Section: Introductionmentioning
confidence: 99%